IMPLEMENTASI PROBLEM BASED LEARNING BERBANTUAN QR CODE DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IX SMP NEGERI 6 SEMARANG - Galuh Setiawati, Shely; Suryadi, Yadi (Penerbit Lafadz Jaya, 2026)
This study describes the implementation of QR Code–assisted Problem Based Learning (PBL) in social studies (IPS) and examines how it supports the development of ninth-grade students’ critical thinking skills at SMP Negeri 6 Semarang. Using a descriptive qualitative design, the study involved an IPS teacher and Grade IX students. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed via data reduction, data display, and conclusion drawing. Credibility was strengthened through source and technique triangulation. Findings show that the learning process followed five PBL stages: problem orientation, organizing students, investigation, developing and presenting solutions, and evaluation/reflection. QR Codes enabled quick access to digital worksheets, curated learning resources, and Padlet for collaborative reporting, which increased engagement and facilitated evidence-based discussion. Students demonstrated stronger critical thinking through (1) analyzing authentic case studies, (2) constructing logical arguments, and (3) evaluating public policies using relevant indicators of development. Supporting factors included the teacher’s facilitative role, a collaborative classroom climate, and meaningful integration of digital media. Constraints involved limited instructional time, uneven literacy levels, and unstable internet connectivity. Overall, QR Code–assisted PBL is effective for creating contextual IPS learning and fostering 21st-century critical thinking skills.